1988
DOI: 10.1079/bjn19880126
|View full text |Cite
|
Sign up to set email alerts
|

Partition of portal-drained visceral net flux in beef steers

Abstract: 1. Blood from chronic indwelling catheters in the caudal aorta and anterior mesenteric, gastrosplenic and hepatic portal veins was used to measure blood flow and net flux of oxygen, glucose and nitrogenous compounds across hepatic portal-drained viscera (PDV), post-stomach (anterior mesenteric-drained viscera (MDV)) and stomach tissues of two beef steers (390 kg mean live weight).2. Steers were fed in sequence on (I) chopped lucerne (Medicago sariva) hay (twelve meals/d), (2) chopped lucerne hay (two meals/d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…From these observations, Dijkstra et al (1992) deduced a relationship with a saturating stimulatory effect of blood urea and an inhibitory effect of rumen ammonia on urea recycling to the rumen. In agreement with this, Reynolds and Huntington (1988) and Huntington et al (1989) observed a reduced stomach net removal of urea from blood to be associated with higher stomach ammonia absorption.…”
Section: Nitrogen/urea Recyclingsupporting
confidence: 74%
See 3 more Smart Citations
“…From these observations, Dijkstra et al (1992) deduced a relationship with a saturating stimulatory effect of blood urea and an inhibitory effect of rumen ammonia on urea recycling to the rumen. In agreement with this, Reynolds and Huntington (1988) and Huntington et al (1989) observed a reduced stomach net removal of urea from blood to be associated with higher stomach ammonia absorption.…”
Section: Nitrogen/urea Recyclingsupporting
confidence: 74%
“…The decline in plasma (and milk) urea N concentration due to the increased urine production must be expected to occur with any Na or K salt (Bannink et al, 1999;Eriksson and Rustas, 2014). In line with Reynolds and Huntington (1988), Spek et al (2013b) observed that the fraction of total urea entry rate that returned to the GIT was negatively related to dietary protein content. Reports on this type of measurements allowed Reynolds and Kristensen (2008), and more recently Batista et al (2017), to demonstrate that GER accounts for almost the entire urea entry rate in systemic blood when dietary DM contains 8% or less CP.…”
Section: Nitrogen/urea Recyclingmentioning
confidence: 82%
See 2 more Smart Citations
“…Resulting from its considerable role in the absorption of nutrients, mainly of short chain fatty acids (SCFAs) and of electrolytes [13], the rumen epithelium ranks among the tissues with high metabolic rates [4, 5]. A main proportion of the rumen ATP utilization is related to activity of a Na + /K + -ATPase that has been shown to be expressed at high levels [68] in the cell membrane of rumen epithelial cells (REC) [9, 10].…”
Section: Introductionmentioning
confidence: 99%